Species-Level Analysis of the Human Gut Microbiome Shows Antibiotic Resistance Genes Associated With Colorectal Cancer - Chuanfa Liu; Chuanfa Liu; Chuanfa Liu; Zhiming Li; Zhiming Li; Jiahong Ding; Jiahong Ding; Hefu Zhen; Hefu Zhen; Mingyan Fang; Mingyan Fang; Chao Nie; et al. (Frontiers in Microbiology, 2021)
Colorectal cancer (CRC) is the second leading cause of cancer deaths and continuously increases new cancer cases globally. Accumulating evidence links risks of CRC to antibiotic use. Long-term use and abuse of antibiotics increase the resistance of the gut microbiota; however, whether CRC is associated with antibiotic resistance in gut microbiota is still unclear. In this study, we performed a de novo assembly to metagenomic sequences in 382 CRC patients and 387 healthy controls to obtain representative species-level genome bins (rSGBs) and plasmids and analyzed the abundance variation of species and antibiotic resistance genes (ARGs). Twenty-five species and 65 ARGs were significantly enriched in the CRC patients, and among these ARGs, 12 were multidrug-resistant genes (MRGs), which mainly included acrB, TolC, marA, H-NS, Escherichia coli acrR mutation, and AcrS. These MRGs could confer resistance to fluoroquinolones, tetracyclines, cephalosporins, and rifamycin antibiotics by antibiotic efflux and inactivation. A classification model was built using the abundance of species and ARGs and achieved areas under the curve of 0.831 and 0.715, respectively. Our investigation has identified the antibiotic resistance types of ARGs and suggested that E. coli is the primary antibiotic resistance reservoir of ARGs in CRC patients, providing valuable evidence for selecting appropriate antibiotics in the CRC treatment.